Molecular characterization of Smtdc-1 and Smddc-1 discloses roles as male-competence factors for the sexual maturation of Schistosoma mansoni females - Li, Xuesong; Weth, Oliver; Haeberlein, Simone; Grevelding, Christoph G. (Frontiers in Cellular and Infection Microbiology, 2023)
Introduction Schistosomes are the only mammalian flatworms that have evolved separate sexes. A key question of schistosome research is the male-dependent sexual maturation of the female since a constant pairing contact with a male is required for the onset of gonad development in the female. Although this phenomenon is long known, only recently a first peptide-based pheromone of males was identified that contributes to the control of female sexual development. Beyond this, our understanding of the molecular principles inducing the substantial developmental changes in a paired female is still rudimentary. Objectives Previous transcriptomic studies have consistently pointed to neuronal genes being differentially expressed and upregulated in paired males. These genes included Smp_135230 and Smp_171580, both annotated as aromatic-L-amino-acid decarboxylases (DOPA decarboxylases). Here, we characterized both genes and investigated their roles in male–female interaction of S. mansoni. Methodologies/findings Sequence analyses indicated that Smp_135230 represents an L-tyrosine decarboxylase (Smtdc-1), whereas Smp_171580 represents a DOPA decarboxylase (Smddc-1). By qRT-PCR, we confirmed the male-specific and pairing-dependent expression of both genes with a significant bias toward paired males. RNA-interference experiments showed a strong influence of each gene on gonad differentiation in paired females, which was enhanced by double knockdown. Accordingly, egg production was significantly reduced. By confocal laser scanning microscopy, a failure of oocyte maturation was found in paired knockdown females. Whole-mount in situ hybridization patterns exhibited the tissue-specific occurrence of both genes in particular cells at the ventral surface of the male, the gynecophoral canal, which represents the physical interface of both genders. These cells probably belong to the predicted neuronal cluster 2 of S. mansoni. Conclusion Our results suggest that Smtdc-1 and Smddc-2 are male-competence factors that are expressed in neuronal cells at the contact zone between the genders as a response of pairing to subsequently control processes of female sexual maturation.